The "new" crisis of the liberal order: Populism, socioeconomic imbalances, and the response of contemporary ordoliberalism - Malte Dold; Tim Krieger (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2019)
In recent years, commentators have noticed that the European liberal order is 'under attack'. Traditional parties of the center are in decline. Populist movements of the right and the left have won elections or significant shares in parliaments. In the face of this 'new' crisis of liberalism, our paper follows the spirit of Walter Lippmann's The Good Society and argues for a renewal of (ordo)liberal thinking. Similar to Lippman - who lamented, "liberalism had become a philosophy of neglect and refusal to proceed with social adaptation" -, we argue that our current liberal economic order is unfit to deal with fundamental social asymmetries. The benefits of open borders and economic integration are distributed unevenly in most societies with urban economic and political elites as main beneficiaries and supporters of the current order, while neglecting less-skilled, rural workers. In this paper, we argue for a contemporary ordoliberalism that takes up this distributional challenge. In spite of recurrent criticism of its value-laden nature, we argue that the normativity of ordoliberalism is actually an asset in the current debate on populism. Moral and ideological arguments are often at the heart of citizens' concerns. Following this rationale, we propose that contemporary ordoliberals advance their thinking in connection with the emerging field of Philosophy, Politics, and Economics (PPE).
Keywords: B25; B31; B41; 330